IMPROVING WRITING SKILL OF STUDENTS OF HOSPITALITY INDUSTRY CONCENTRATION PROGRAM OF SRIWIJAYA STATE POLYTECHNIC THROUGH WEBLOG - Risa - (Politeknik Negeri Sriwijaya, 2014)
This study investigated the improvement in writing skill through weblog. It was aimed at finding out whether or not there is a significant difference in writing achievements between the students who have treatment and that of those who have not, and how much weblog contributes in improving students’ writing achievements. Forty out of 99 second semester students in the academic year 2011/2012 of Hospitality Industry Concentration Program of English Department Sriwijaya State Polytechnic were selected as the samples based on the criteria: (1) their average score of their reading and writing between 66 – 85, (2) their TOEIC score was between 255 – 600, and (3) they were taught by the same lecturer. They were divided into two groups that consisted of 20 students for experimental group and 20 students for control group. All samples were given writing tests based on the suitable topics of their major. T-test and regression analysis were used in analyzing the data. The results showed that the students who had treatment achieved higher and better scores in their writing compared to the students who had not. This study found out that weblog gives much contribution in improving the students’ writing achievements.